Natural Compounds and PCL Nanofibers: A Novel Tool to Counteract Stem Cell Senescence - Bellu, Emanuela; Cruciani, Sara; Garroni, Giuseppe; Balzano, Francesca; Satta, Rosanna; Montesu, Maria Antonia; Fadda, Angela; Mulas, Maurizio; Sarais, Giorgia; Bandiera, Pasquale; Ventura, Carlo; Kralovič, Martin; et al. (Cells, 2021)
Tissue homeostasis mainly depends on the activity of stem cells to replace damaged elements and restore tissue functions. Within this context, mesenchymal stem cells and fibroblasts are essential for maintaining tissue homeostasis in skin, in particular in the dermis. Modifications in collagen fibers are able to affect stem cell features. Skin properties can be significantly reduced after injuries or with aging, and stem cell niches, mainly comprising extracellular matrix (ECM), may be compromised. To this end, specific molecules can be administrated to prevent the aging process induced by UV exposure in the attempt to maintain a youngness phenotype. NanoPCL-M is a novel nanodevice able to control delivery of Mediterranean plant myrtle (Myrtus communis L.) extracts. In particular, we previously described that myrtle extracts, rich in bioactive molecules and nutraceuticals, were able to counteract senescence in adipose derived stem cells. In this study, we analyzed the effect of NanoPCL-M on skin stem cells (SSCs) and dermal fibroblasts in a dynamic cell culture model in order to prevent the effects of UV-induced senescence on proliferation and collagen depot. The BrdU assay results highlight the significantly positive effect of NanoPCL-M on the proliferation of both fibroblasts and SSCs. Our results demonstrate that-M is able to preserve SSCs features and collagen depot after UV-induced senescence, suggesting their capability to retain a young phenotype.
Keywords: fytonutrienty; Humans; Stem Cells; Phytochemicals; Cellular Senescence; Adipose Tissue; Nanofibers; tuková tkáň; stárnutí buněk; rostlinné extrakty; Plant Extracts; fibroblasty; Fibroblasts; Myrtus; lidé; nanovlákna; kmenové buňky